A Temporal–Spatial Atlas of Peripheral Nerve Evoked Cortex Potential in Rat: A Novel Testbed to Explore the Responding Patterns of the Brain to Peripheral Nerves. (July 2022) - Yin, Xiaofeng; Deng, Jiuxu; Chen, Bo; Jin, Bo; Gu, Xinyi; Qi, Zhidan; Leng, Kunpeng; Jiang, Baoguo
Abstract: Observing the dynamic progress of the brain in response to peripheral nerve stimulation as a whole is the basis for a deeper understanding of overall brain function; however, it remains a great challenge. In this work, a novel mini-invasive orthogonal recording method is developed to observe the overall evoked cortex potential (ECP) in rat brain. A typical ECP atlas with recognizable waveforms in the rat cortex corresponding to the median, ulnar, and radial nerve trunks and subdivided branches is acquired. Reproducible exciting temporal–spatial progress in the rat brain is obtained and visualized for the first time. Changes in the ECPs and exciting sequences in the cortex four months after median nerve transection are also observed. The results suggest that the brain's response to peripheral stimulation has precise and reproducible temporal–spatial properties. This resource can serve as a testbed to explore the overall functional interaction and dynamic remodeling mechanisms between the peripheral and central nervous systems over time.